KAJIAN PENGARUH KINERJA KEUANGAN DAN KEBIJAKAN HUTANG TERHADAP PERGERAKAN HARGA SAHAM PADA PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - noerchoidah, noerchoidah; Harryono, Sumadji; Perdana, Buyung Cahya (Majalah Ekonomi, 2019)
For instance, in form of a deposit with average of 6 % per annum, stock exchange investment gives return more than saving money in bank. But investor must be analyze carefully in buying shares. Using one analytical share techniques method. Investor will easily know which share they should buy. This research attempt to observe whether financial performance of the firms in analyzing the share of food and beverage company in Indonesian stock exchange still has strong influence to their shares prices movement. Financial performance variables which have direct relationship to share, Divident per share, Price Earning, Debt to Equity and Return in Equity and they are as part of leverage variables of the firm. Analysis shows that from the five independent variables of financial performance which are tested individually, only divident per share influence shares price movement. When they are tested simultaneously, all of them influence shares prices movement significantly but this this shares prices movement is effected by independent variables while the others caused by non fundamental factors of the firms.